T1ρ mapping for assessment of renal allograft fibrosis. Issue 4 (21st January 2019) - Hectors, Stefanie J.; Bane, Octavia; Kennedy, Paul; El Salem, Fadi; Menon, Madhav; Segall, Maxwell; Khaim, Rafael; Delaney, Veronica; Lewis, Sara; Taouli, Bachir
Abstract : Background: There is an unmet need for noninvasive methods to diagnose and stage renal allograft fibrosis. Purpose: To investigate the utility of T1ρ measured with MRI for the assessment of fibrosis in renal allografts. Study Type: Institutional Review Board (IRB)‐approved prospective. Subjects: Fifteen patients with stable functional allograft (M/F 9/6, mean age 56 years) and 12 patients with allograft dysfunction and established fibrosis (M/F 6/6, mean age 51 years). Field Strength/Sequence: T1ρ imaging at 1.5T using a custom‐developed sequence. Assessment: Average T1ρ in the cortex and medulla was quantified and T1ρ repeatability (expressed by the coefficient of variation [CV]) was measured in four patients. Statistical Tests: Differences in T1ρ values between the 2 groups were assessed using Mann–Whitney U ‐tests. Diagnostic performance of T1ρ for differentiation between functional and fibrotic allografts was evaluated using receiver operating characteristic (ROC) analysis. Spearman correlations of T1ρ with Masson's trichrome‐stained fractions and serum estimated glomerular filtration rate (eGFR) were assessed. Results: Higher T1ρ repeatability was found for cortex compared with medulla (mean CV T1ρ cortex 7.4%, medulla 13.3%). T1ρ values were significantly higher in the cortex of fibrotic vs. functional allografts (111.8 ± 17.2 msec vs. 99.0 ± 11.0 msec, P = 0.027), while there was no difference in medullary T1ρ values (122.6 ± 20.8 msec vs. 124.3 ± 20.8 msec, P = 0.789). Cortical T1ρ significantly correlated with Masson's trichrome‐stained fractions ( r = 0.515, P = 0.044) and eGFR ( r = –0.546, P = 0.004), and demonstrated an area under the curve (AUC) of 0.77 for differentiating between functional and fibrotic allografts (sensitivity and specificity of 75.0% and 86.7%, using threshold of 106.9 msec). Data Conclusion: Our preliminary results suggest that T1ρ is a potential imaging biomarker of renal allograft fibrosis. These results should be verified in a larger study. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1085–1091.